The 1978 Canadian Video Open. - Craig, Kate; Dyson, Brian; Gale, Peggy; Robertson, Clive (Calgary : Arton's, 1978)
Barling, Marion ; Berteig, Garry ; Black, Byron ; Britton, Susan ; The Dishes ; Druick, Don ; Fox, Charlie ; Free, John ; General idea ; Gentleman, Ross ; Goldman, Saul ; Harding, Noel ; HP ; Huggler, Carol ; Hutchinson, Nora ; Image Bank ; Jeffries, Bill ; Kuramoto, Ken ; Lewis, Glenn ; MacHattie, Keith ; Marshalore ; McGlade, Terry ; Dundas, Sally ; Morris, Mark ; Robertson, Clive ; Sherman, Tom ; Simpson, Gregg ; Steinman, Barbara ; Tranter, Barbara ; Sterloff, Wayne ; Vanderzaag, Elizabeth ; Ward, Rick ; Werden, Rodney ; Wimcharuk, Kate ; Zablockis, Raymond ; Young, Robert
The 1978 Canadian Video Open, Arton's, Calgary, 1978
boek